Realizing sustainable development goal 4 (SDG 4): Examining quality processes, content, and outcomes in higher education students - Yanuarto, Wanda Nugroho; Setyaningsih, Eka; Hapsari, Ira; Fukui, Masanori (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study explores how Sustainable Development Goal 4 (SDG 4), which emphasises inclusive, equitable, and quality education, is implemented in the context of Indonesian higher education. It focuses on how the quality of teaching processes, curriculum content, and student learning outcomes interact to shape meaningful learning experiences. Method: A cross-sectional quantitative design was used, involving 638 university students from Universitas Muhammadiyah Purwokerto, Indonesia. Data were collected through a structured questionnaire and analysed using Structural Equation Modelling (SEM-AMOS) to examine both direct and indirect relationships among instructional practices, curriculum relevance, and learning achievement. Findings: The analysis showed a strong and positive connection between the quality of educational processes and student outcomes. However, weaker or even negative links were observed between process quality and content, as well as between content and outcomes, suggesting that good teaching practices alone are insufficient without a coherent and relevant curriculum design. Significance: This study deepens the understanding of SDG 4 by showing how pedagogy and curriculum alignment jointly contribute to learning equity in universities. The findings offer practical insights for educators and policymakers striving to enhance teaching quality and inclusiveness in higher education.